Microstrip Patch Antenna Design for Natural Rubber Permittivity Detection - Abdul Kadar, Muhammad Sazlan; Mohd Muji, Siti Zarina; Ikhsan, Fatin Hamimah; Joret, Ariffuddin; Yee, See Khee; Che Seman, Fauziahanim; Abdul Rahim, Ruzairi; Othman, Nadras (International Journal of Integrated Engineering, 2025)
This paper presents a simulation-based analysis on a rectangular microstrip patch antenna sensor capable of detecting changes in natural rubber (NR) permittivity using CST Microwave Studio. In this work, the patch antenna sensor was designed with a gap distance of 1.0 mm, 1.5 mm, and 2.0 mm between the patch and the feeder, which affects the resonance characteristics of the antenna and enhances the interaction between its radiated waves and the NR, which is the Material Under Test (MUT). As the dielectric properties were disposed of between 2.7 to 4.8 according to the experimental observable (using vector network analyzer (VNA) and dielectric probe) for NR samples in simulation model. This could be helpful in designing to see how the gap distance affects the resonant frequency shift of the antenna, return loss, and sensitivity. The 2.0 mm gap configuration in this study has the highest sensitivity of -0.0072 GHz/ε with the linear measurement rate of 0.9979, which is more sensitive to the changes of dielectric. Therefore, these results verify the capability of the microstrip patch antenna sensor for precise and dependable permittivity detection in agriculture applications.